(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article examines the scientific and pedagogical significance of shadow boxing exercises in the development of boxers’ technical and tactical skills. The study analyzes the impact of shadow boxing on movement coordination, punching technique, tactical thinking, and decision-making speed during a bout. Based on pedagogical observation, comparative analysis, and experimental methods, the results indicate that systematic inclusion of shadow boxing exercises in the training process enhances the automation of technical actions and improves the tactical preparedness of boxers. The article scientifically substantiates the role of shadow boxing within the structure of the educational and training process.